2015
DOI: 10.1037/xan0000046
|View full text |Cite
|
Sign up to set email alerts
|

Temporal distributions of schedule-induced licks, magazine entries, and lever presses on fixed- and variable-time schedules.

Abstract: In this article, schedule-induced drinking (SID) refers to increased drinking by hungry rats exposed to intermittent delivery of food pellets. Two major accounts of SID differ in their explanation of why such drinking tends be concentrated soon after pellet delivery. Temporal discrimination theories propose that drinking is a form of displacement activity that occurs when a pellet is least likely. Adventitious reinforcement theories propose that drinking is displaced to early in an interpellet interval (IPI) b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…The first peak is not very interesting from the point of view of the learning mechanisms involved, but the second peak is (see Boakes, Patterson, Kendig, & Harris, 2015, for similar results with constant FT 30-s schedules), as it can be presumed to compete with drinking (e.g., Aristizabal, Callejas-Aguilera, Ogallar, Pellón, & Rosas, 2015;but see below). Competition between licking a waterspout and magazine entering is a normal finding in temporal schedules (e.g., Reid & Dale, 1983), as well as for other operant responses (Dragoi & Staddon, 1999), and in the present results, it can be seen how distributions of licking (see Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The first peak is not very interesting from the point of view of the learning mechanisms involved, but the second peak is (see Boakes, Patterson, Kendig, & Harris, 2015, for similar results with constant FT 30-s schedules), as it can be presumed to compete with drinking (e.g., Aristizabal, Callejas-Aguilera, Ogallar, Pellón, & Rosas, 2015;but see below). Competition between licking a waterspout and magazine entering is a normal finding in temporal schedules (e.g., Reid & Dale, 1983), as well as for other operant responses (Dragoi & Staddon, 1999), and in the present results, it can be seen how distributions of licking (see Fig.…”
Section: Discussionmentioning
confidence: 95%
“…However, the 50 % contingency group was the one that showed the highest level of magazine entries, more than the 0 % contingency rats; thus, the order in which animals engaged in licking cannot be attributed solely to competition from magazine entries (despite the master rats showing the highest licking and the lowest entries; see also Boakes et al, 2015). In general, during Phase 1, licks increased as sessions progressed but magazine entries did not decrease (see the lack of an effect of sessions for magazine entries in the Results section; see also Kirkpatrick & Church, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with magazine training experiments [e.g. 38,39], we compared this response rate during the presentation of a cue with the response rate immediately before its presentation. The final dependent variable used in the statistical analyses was the proportion of time participants spent looking at the correct goal area during the cue presentation before outcome onset (cue interval) minus the gaze time at the same goal area during an equally long interval before cue onset (pre-cue interval).…”
Section: Plos Onementioning
confidence: 99%
“…
Boakes, Patterson, Kendig, and Harris (2015) showed that schedule-induced drinking (SID), typically concentrated in the first half of the interpellet interval, is not moved there exclusively by competition from magazine entries, and that not all arbitrary responses can be maintained by adventitious reinforcement. They attribute such inferences to Killeen and Pellón (2013) and Patterson and Boakes (2012), and on that basis reject their explanation for the excessive nature of many adjunctive responses as a result of reinforcement.
…”
mentioning
confidence: 99%